Measuring Success in Focused Deterrence Through an Effective Researcher-Practitioner Partnership, Philadelphia, PA, 2003-2015 - Roman, Caterina Gouvis ([Verlag nicht ermittelbar], 2021)
In the fall of 2013, Temple University's Department of Criminal Justice was awarded a research grant by the National Institute of Justice to evaluate Philadelphia's Focused Deterrence (FD) strategy. The study was designed to provide a comprehensive, objective review of FD and to determine if the law enforcement partnership accomplished what it set out to accomplish. The findings from this study highlight the key results from the impact evaluation that assessed whether gun violence saw a statistically significant decline that could be attributed to FD. The impact evaluation focused on area-level reductions in shootings. The evaluation uses victim and incident data from 2003 through March 2015 received from Philadelphia Police Department. The post-FD period of examination consists of the first 24 months after the implementation of FD (April 2013 through March 2015).